Optimization of medium components for the production of ectoine by a halophilic bacterium isolated from Can Gio mangrove - Thuoc, Doan Van; Hien, Tran Thi (Vietnam Journal of Science and Technology, 2019)
The effect of different carbon and nitrogen sources on growth of producer strain was investigated. Sucrose and glucose were found to be suitable carbon sources, and monosodium glutamate was favorable nitrogen source for bacterial cell growth. Optimum salt concentrations for bacterial growth was ranged from 4 to 6%, whereas, NaCl concentrations from 12 to 15% found to be good for ectoine accumulation. Two-step fed-batch fermentation was then designed, biomass and ectoine content were significant increased, maximum CDW of 25 g/l and ectoine content of 10.3% were obtained.